PANDAS/PANS in childhood: Controversies and evidence. Issue 2 (9th December 2018) - Wilbur, Colin; Bitnun, Ari; Kronenberg, Sefi; Laxer, Ronald M; Levy, Deborah M; Logan, William J; Shouldice, Michelle; Yeh, E Ann
Abstract: Since first defined in 1998, paediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) and its later, broader iteration, paediatric acute-onset neuropsychiatric syndrome (PANS), have garnered significant attention and controversy. The role of streptococcal infection in children with explosive onset obsessive-compulsive disorder and new onset tics, the natural history of this entity, and the role of symptomatic and disease-modifying therapies, including antibiotics, immunotherapy, and psychoactive drugs, are all issues that have yet to be definitively addressed. While definitive proof of the autoimmune hypothesis of PANDAS is lacking, given the heightened attention to this entity and apparent rise in use of this diagnostic category, addressing questions around diagnosis, treatment, and etiology is imperative. In this paper, we review current working definitions of PANDAS/PANS, discuss published evidence for interventions related to this entity, and propose a clinical approach to children presenting with acute symptoms satisfying criteria for PANDAS/PANS.